2020
DOI: 10.1093/femsec/fiaa048
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of copper and lead exposure on prokaryotic communities from contaminated contrasted coastal seawaters: the influence of previous metal exposure

Abstract: Our understanding of environmental factors controlling prokaryotic community is largely hampered by the large environmental variability across spatial scales (e.g. trace metal contamination, nutrient enrichment and physicochemical variations) and the broad diversity of bacterial pre-exposure to environmental factors. In this article, we investigated the specific influence of copper (Cu) and lead (Pb) on prokaryotic communities from the uncontaminated site, using mesocosm experiments. In addition, we studied ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 79 publications
(100 reference statements)
3
7
0
Order By: Relevance
“…Overall, abiotic variables were stable through the one-month experiment in June 2015, and no significant differences between surface and bottom seawater were observed. However, we found that TM concentrations exhibited strong north-south decreasing gradients, as previously observed punctually, monthly, or pluri-annually in Toulon Bay (Coclet et al, 2018(Coclet et al, , 2019(Coclet et al, , 2020Layglon et al, 2020), allowing us to specifically address the potential effect of TM on the structure and functions of prokaryotic biofilm communities. The high contamination levels of localized areas indicated significant anthropogenic inputs that could be attributed to numerous recent (e.g., large boat traffic, harbor activities, antifouling coatings, sediment remobilization) (Turner, 2010;Layglon et al, 2020), and historical events (2nd World War) (Tessier et al, 2011).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Overall, abiotic variables were stable through the one-month experiment in June 2015, and no significant differences between surface and bottom seawater were observed. However, we found that TM concentrations exhibited strong north-south decreasing gradients, as previously observed punctually, monthly, or pluri-annually in Toulon Bay (Coclet et al, 2018(Coclet et al, , 2019(Coclet et al, , 2020Layglon et al, 2020), allowing us to specifically address the potential effect of TM on the structure and functions of prokaryotic biofilm communities. The high contamination levels of localized areas indicated significant anthropogenic inputs that could be attributed to numerous recent (e.g., large boat traffic, harbor activities, antifouling coatings, sediment remobilization) (Turner, 2010;Layglon et al, 2020), and historical events (2nd World War) (Tessier et al, 2011).…”
Section: Discussionsupporting
confidence: 60%
“…Rather than the atmospheric pathway, TM seawater contamination of the semi-enclosed Toulon Bay (Mediterranean Sea, France) is primarily caused by urban and industrial wastes (Levin et al, 2001;Oursel et al, 2013), antifouling coatings (Turner, 2010), fuel consumption (Callender, 2003), and sediment resuspension (Dang et al, 2015;Layglon et al, 2020). Then, seawater of the Toulon Bay is characterized by high levels of anthropogenic (Cd, Pb, and Zn) and intermediate (i.e., both anthropogenic and natural origins) (Cu and Ni) TMs (Jean et al, 2012;Coclet et al, 2018Coclet et al, , 2019Coclet et al, , 2020Layglon et al, 2020), which can be 100-fold above geochemical background levels of the Mediterranean Sea (Morley et al, 1997), and by far, upper than most of Mediterranean coastal zones (Cossa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Copper contamination from harbors has been proved to be highly toxic for planktonic microorganisms (Coclet et al, 2020(Coclet et al, , 2018. Lead (Pb) contamination is mostly archived in harbors sediment, often originating from older sources such as coal combustion, battery factories, metal smelting, leaded gasoline.…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of TMs in Toulon-bay have been reported as being of the same order of magnitude or even higher than strongly impacted aquatic ecosystems (Pringault et al, 2012;Misson et al, 2016), with a decreasing gradient from the most anthropized parts to the open waters of the Mediterranean Sea. Along this gradient, bacterioplankton composition is shaped, including shifting the autotrophic community from picoeukaryote dominated community in the most contaminated parts to cyanobacteria (more representative of the open ocean) in less impacted areas (Coclet et al, 2018(Coclet et al, , 2019(Coclet et al, , 2020. Alongside TMs pollution, an important amount of MPs can be found in the surface water of Toulon bay, with an average of 32 800 MPs/km-2 (Tesan- Onrubia et al;2021).…”
Section: Seawater Copper Content Controls Biofilm Bioaccumulation and Microbial Community On Microplasticsmentioning
confidence: 99%
“…The sampling locations were chosen based on the long-time monitoring of trace metals performed in the area, highlighting contrasted Cu concentrations in the considered locations (Tessier et al, 2011Coclet et al, 2018Coclet et al, , 2019Coclet et al, , 2020. Pt12 sampling station is located in the enclosed part of the bay of Toulon, near the main harbour, therefore submitted to important metallic inputs from the anthropogenic activities (Fig.…”
Section: Seawater Sampling and Bioassay Experimentsmentioning
confidence: 99%